Effectiveness of Different Training Modalities on Static Balance in Older Adults: A Systematic Review and Meta-Analysis - Noé Labata-Lezaun; Sergi Rodríguez-Rodríguez; Carlos López-de-Celis; Jacobo Rodríguez-Sanz; Max Canet-Vintró; Guillermo R.-Oviedo; Vanessa González-Rueda; Albert Pérez-Bellmunt (Life, 2023)
(1) Background: aging is associated with functional changes such as balance, which plays a critical role in older adults. Physical exercise has been established as a factor capable of modulating these age-related alterations. (2) Methods: a meta-analysis of randomized clinical trials (RCTs) was conducted. The systematic search was performed in the PubMed/MEDLINE, Web of Science, the SPORTDiscus and Cochrane Library databases. Articles were included if participants were 65 years or older, healthy and performing resistance training, aerobic training, balance training or multicomponent training. Studies were excluded if there was a combination of training with other types of intervention. The protocol of this systematic review was published in the International Prospective Register of Systematic Reviews (PROSPERO) with the code CRD42021233252 (3) Results: the search strategy found a total of 1103 studies. After removing duplicates and the inclusion and exclusion criteria, eight articles were included in the meta-analysis, with a total of 335 healthy older adults analyzed. The results showed no significant differences between the intervention groups and the control groups after the exercise programs. (4) Conclusions: interventions based on different types of exercise improved static balance in elderly population, but without statistically significant difference in comparison with the control groups.